2006
DOI: 10.1111/j.1574-6968.2006.00503.x
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coliis naturally transformable in a novel transformation system

Abstract: A novel transformation system, in which neither a nonphysiological concentration of Ca2+ and temperature shifts nor electronic shocks were required, was developed to determine whether Escherichia coli is naturally transformable. In the new protocol, E. coli was cultured normally to the stationary phase and then cultured statically at 37 degrees C in Luria-Bertani broth. After static culture, transformation occurred in bacteria spread on Luria-Bertani plates. The protein synthesis inhibitor chloramphenicol inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 22 publications
6
49
2
Order By: Relevance
“…This observation contrasts the studies reporting the ability of some bacterial species present in the GIT to become naturally transformed in vitro (Mercer et al, 1999a;Sun et al, 2006). Likely explanations for this non-uniform knowledge state include: (i) methodological limitations to the GIT sample size that can be practically analyzed for low frequency transfer events; (ii) a lack of understanding of ecological processes in the GIT limiting our ability to design biologically and tempo-spatially relevant HGT investigations; (iii) unidentified processes in the GIT that shields or adsorb DNA molecules during degradation process preventing measurable exposure to competent bacteria; or (iv) lack of competence development in naturally transformable bacteria in the GIT.…”
Section: Discussioncontrasting
confidence: 94%
“…This observation contrasts the studies reporting the ability of some bacterial species present in the GIT to become naturally transformed in vitro (Mercer et al, 1999a;Sun et al, 2006). Likely explanations for this non-uniform knowledge state include: (i) methodological limitations to the GIT sample size that can be practically analyzed for low frequency transfer events; (ii) a lack of understanding of ecological processes in the GIT limiting our ability to design biologically and tempo-spatially relevant HGT investigations; (iii) unidentified processes in the GIT that shields or adsorb DNA molecules during degradation process preventing measurable exposure to competent bacteria; or (iv) lack of competence development in naturally transformable bacteria in the GIT.…”
Section: Discussioncontrasting
confidence: 94%
“…Although several studies of Escherichia coli have identified conserved homologues of all genes required by most competent bacteria to take up DNA (12,15,22,59), researchers have for decades struggled to demonstrate that E. coli takes up and recombines chromosomal DNA, and introduction of plasmids into E. coli cells relies on artificial permeabilization by calcium chloride or on electroporation. Although more "natural" variants of these techniques have been reported (7,8,10,82), no competence genes have been implicated, and a recent study found that plasmid transformation of E. coli on agar plates does not require four putative competence genes whose homologues are essential for DNA uptake in other bacteria (70).…”
mentioning
confidence: 99%
“…In this study, natural transformation of E. coli isolates was done using the transformation system described by Sun et al [8]. The results demonstrated that the integron-containing DNA from the seven donors could be transferred to E. coli J53Az r in this transformation system with the transformation frequency of 10 -7 to 10 -5 ( Table 3).…”
Section: Natural Transformationmentioning
confidence: 89%
“…The plasmids isolated from seven integron-positive strains were subjected to natural transformation with E. coli J53Az r as the recipient followed the previously described protocol [8]. The recipient strain was grown overnight in LB broth (to reach a density of 10…”
Section: Natural Transformation Of E Colimentioning
confidence: 99%
See 1 more Smart Citation